Effects of Sub-lethal Concentrations of Silver Nanoparticles on a Simulated Intestinal Prokaryotic–Eukaryotic Interface - Garuglieri, Elisa; Meroni, Erika; Cattò, Cristina; Villa, Federica; Cappitelli, Francesca; Erba, Daniela (Frontiers in Microbiology, 2018)
Nanotechnology applications are expected to bring a range of benefits to the food sector, aiming to provide better quality and conservation. In this research, the physiological response of both an Escherichia coli mono-species biofilm and Caco-2 intestinal cells to sub-lethal concentrations of silver nanoparticles (AgNPs) has been investigated. In order to simulate the anaerobic and aerobic compartments required for bacteria and intestinal cells growth, a simplified semi-batch model based on a transwell permeable support was developed. Interaction between the two compartments was obtained by exposing Caco-2 intestinal cells to the metabolites secreted by E. coli biofilm after its exposure to AgNPs. To the best of the authors’ knowledge, this study is the first to investigate the effect of AgNPs on Caco-2 cells that takes into consideration previous AgNP-intestinal biofilm interactions, and at concentrations mimicking real human exposure. Our data show that 1 μg/mL AgNPs in anaerobic conditions i) promote biofilm formation up to 2.3±0.3 fold in the first 72 h of treatment; ii) increase ROS production to 84±21% and change the physiological status of microbial cells after 96 h of treatment; iii) seriously affect a 72-h old established biofilm, increasing the level of oxidative stress to 86±21%. Moreover, the results indicate that oxygen renders the biofilm more adequate to counteract AgNP effects. Comet assays on Caco-2 cells demonstrated a protective role of biofilm against the genotoxic effect of 1 μg/mL AgNPs on intestinal epithelial cells.